Infantile Hypertrophic Pyloric Stenosis in Postoperative Esophageal Atresia with Tracheoesophageal Fistula - Hassan RAA; Choo YU; Noraida R; Rosida I (EL-Med-Pub, 2015)
Development of infantile hypertrophic pyloric stenosis during postoperative period in EA with TEF is rare. Postoperative vomiting or feeding intolerance in EA is more common which is due to esophageal stricture, gastroesophageal reflux and esophageal dysmotility. A typical case of IHPS also presents with non-bilious projectile vomiting at around 3-4 weeks of life. The diagnosis of infantile hypertrophic pyloric stenosis in this subset is usually delayed because of its rarity. We report a case of IHPS in postoperative EA and emphasize on high index of suspicion to avoid any delay in diagnosis with its metabolic consequences.